Overexpression of Karrikins Receptor Gene Sapium sebiferum KAI2 Promotes the Cold Stress Tolerance via Regulating the Redox Homeostasis in Arabidopsis thaliana - Shah, Faheem Afzal; Ni, Jun; Yao, Yuanyuan; Hu, Hao; Wei, Ruyue; Wu, Lifang (Frontiers in Plant Science, 2021)
KARRIKINS INSENSITIVE2 (KAI2) is the receptor gene for karrikins, recently found to be involved in seed germination, hypocotyl development, and the alleviation of salinity and osmotic stresses. Nevertheless, whether KAI2 could regulate cold tolerance remains elusive. In the present study, we identified that Arabidopsis mutants of KAI2 had a high mortality rate, while overexpression of, a bioenergy plant, Sapium sebiferum KAI2 (SsKAI2) significantly recovered the plants after cold stress. The results showed that the SsKAI2 overexpression lines (OEs) had significantly increased levels of proline, total soluble sugars, and total soluble protein. Meanwhile, SsKAI2 OEs had a much higher expression of cold-stress-acclimation-relate genes, such as Cold Shock Proteins and C-REPEAT BINDING FACTORS under cold stress. Moreover, the results showed that SsKAI2 OEs were hypersensitive to abscisic acid (ABA), and ABA signalling genes were w significantly affected in SsKAI2 OEs under cold stress, suggesting a potential interaction between SsKAI2 and ABA downstream signaling. In SsKAI2 OEs, the electrolyte leakage, hydrogen peroxide, and malondialdehyde contents were reduced under cold stress in Arabidopsis. SsKAI2 OEs enhanced the anti-oxidants like ascorbate peroxidase, catalase, peroxidase, superoxide dismutase, and total glutathione level under cold stress. Conclusively, these results provide novel insights into the understanding of karrikins role in the regulation of cold stress adaptation.